mTOR在肺类癌中的研究进展 (Zhongguo Fei Ai Za Zhi, 2013)
Mammalian target of rapamycin (mTOR), a main protein kinase in the phosphoinositide 3-kinase (PI3K)/AKT/mTOR signaling pathway, is an important intracellular mediator involved in multiple celluar functions including proliferation, differentiation, apoptosis, tumorigenesis, and angiogenesis. Recently, the high expression of mTOR and mTOR-related kinase have been found in neuroendocrin tumors. Therefore, mTOR pathway represents an attractive target for new anticancer therapies except surgery.